Gender-Based Violence Against Trans* Individuals: A Netnography of Mary Gregory’s Experience in Powerlifting - Taha-Thomure, Raiya; Milne, Aalaya S.; Kavanagh, Emma J.; Stirling, Ashley E. (Frontiers in Psychology, 2022)
The trans* identity, asterisk included, represents the spectrum of identities who do not conform with hegemonic understandings of a binary gender assigned at birth. Trans* individuals are among the most vulnerable populations, with an estimated 40% of trans* people experiencing physical assault, and 50% experiencing sexual assault within their lifetimes (Stotzer, 2009). Previous research has identified characteristics such as sex, perceived gender, gender identity, race, immigration status, and ability level, in addition to the possible overlap and intersections of such, as factors that may influence athletes’ susceptibility to experiencing violence in sport (Crooks et al., 2019; McPherson et al., 2017 Ohlert et al., 2018; Rhind & McDermott, 2020; Stalker & McArthur, 2012; Sugarman et al., 2018; Vertommen et al., 2016). Gender-based violence (GBV), referring specifically to violence directed at someone due to their gender expression, gender identity and/or perceived gender (Government of Canada, 2019), experienced specifically by trans* individuals in the context of sport has received limited research attention. The purpose of this study, therefore, was to examine discourses of GBV and inequities faced by trans* powerlifter, Mary Gregory, following her expulsion from the 100% Raw Powerlifting Federation (Maese, 2019). This research used an ethnographic case study design of online media. Data were collected and analyzed from online news sources, as well as social media platforms, including Instagram, Twitter, and YouTube. The data provided an insight into the cyberculture of powerlifting, and the negotiation of space, or lack thereof, for trans* athletes within this physical culture. Five themes of gender-based violence against trans* individuals (GBV-T*) were generated, including invalidation of gender identity, dehumanization, infliction of derogatory and crude language, accusations of cheating, and being compared to cisgender athletes without nuance. The study highlights the presence of significant vitriol across virtual platforms directed at Gregory and the underlying presence of negative trans* discourse. This case provides examples of normalized transphobia in sport, a lack of readiness to accept trans* athletes, and concerns for the safety of trans* athletes in sporting spaces.